THE EFFECT OF INFLATION, EDUCATION LEVEL AND GROSS REGIONAL DOMESTIC PRODUCT (GRDP) ON THE MINIMUM WAGE IN JAVA: PENGARUH INFLASI, TINGKAT PENDIDIKAN DAN PRODUCT DOMESTIC REGIONAL BRUTO (PDRB) TERHADAP UPAH MINIMUM DI PULAU JAWA - Widya Meinita; Saparuddin Mukhtar; Ari Saptono (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
This study aims to determine the effect of inflation, Education Level, Gross Regional Domestic Product (GRDP) on the Minimum Wage. The data used in each variable uses secondary data, namely inflation rate, average length of schooling, gross regional domestic product and provincial minimum wages from provinces in Java, namely Banten, DKI Jakarta, West Java, Central Java, D.I. Yogyakarta and Java. East for 5 years from 2015-2019. The data analysis technique used regression analysis using the Fixed Effect Model. The results showed that the level of education and gross domestic product had a positive and significant effect on the provincial minimum wage. While the level of work participation has a positive and insignificant effect on the provincial minimum wage